2016
DOI: 10.1248/cpb.c16-00682
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity and Molecular Geometry of Some New Symmetrical Tris(aminoalkyl)amine Derivatives

Abstract: We report the preparation of new tripodal receptor-type C 3 -and C S -symmetrical molecules constructed on a tris(2-aminoethyl)amine (TAEA) template. Both the anti-herpes simplex virus type 1 (anti-HSV-1) activity and cytotoxic activity of synthesized receptor-type derivatives were evaluated in order to find a characteristic structural feature for these bioactivities of compounds. Among the compounds of synthesized symmetrical TAEA-related derivatives, compound 13k showed high anti-HSV-1 activity (50% effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The purification to obtain spectroscopically pure compounds was easily achieved via simple precipitation and the recrystallisation of the hydrochloride salts. To our knowledge, the synthesis of compounds 1a-5a is reported here for the first time, except for 3a, which was described before by Sumoto's group [26], but with a different procedure to the one reported here. The 1 H, 13 C, and ATR-IR spectra of the new compounds, as well as the X-ray diffraction structure of compound 3a, can be found in the Electronic Supplementary Materials.…”
Section: Synthesismentioning
confidence: 94%
See 1 more Smart Citation
“…The purification to obtain spectroscopically pure compounds was easily achieved via simple precipitation and the recrystallisation of the hydrochloride salts. To our knowledge, the synthesis of compounds 1a-5a is reported here for the first time, except for 3a, which was described before by Sumoto's group [26], but with a different procedure to the one reported here. The 1 H, 13 C, and ATR-IR spectra of the new compounds, as well as the X-ray diffraction structure of compound 3a, can be found in the Electronic Supplementary Materials.…”
Section: Synthesismentioning
confidence: 94%
“…Another group of bioactive compounds bearing this moiety is psychoactive and stimulant drugs [24,25]. There are also examples of its derivatives that show antimicrobial activity [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…4 To develop new multivalent symmetrical bioactive compounds or leads, we have recently designed and synthesized a few new molecules with such geometry and evaluated their bioactivities in order to find new types of bioactive leads. [5][6][7][8][9][10][11][12][13][14] In connection with this project, we have recently reported the preparation of various C3-symmetrical trivalent 1,3,5-triazine (TAZ) derivatives and the results of biological evaluation of the synthesized symmetrical TAZ derivatives. 7,12 Among previously targeted C3-symmetrical TAZ derivatives, we found that C3-symmetrical tri-substituted TAZ derivatives (A and B) showed high levels of anti-HSV-1 activity (EC50 = 0.98 and 1.87 μM, respectively) and considerably low levels of cytotoxic activity (CC50 > 200 μM) against Vero cells, 7,12 and these TAZ derivatives are considered to be potential new leads in the search for antiviral active molecules (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To develop new multivalent symmetrical bioactive compounds or leads, we have recently designed and synthesized a few new molecules with such geometry and evaluated their bioactivities in order to find new types of bioactive leads. [3][4][5][6][7][8][9][10][11][12][13][14] In connection with this project, we have recently reported the preparation of various C3-symmetrical trivalent 1,3,5triazine (TAZ) derivatives and the results of biological evaluation of the synthesized symmetrical TAZ derivatives. 5,11 Among previously targeted C3-symmetrical TAZ derivatives, we found that C3-symmetrical tri-substituted TAZ derivative 3d-H (A) showed a high level of anti-HSV-1 activity (EC50 = 0.98 μM) and a considerably low level of cytotoxic activity (CC50 => 200 μM) against Vero cells.…”
mentioning
confidence: 99%